2020
DOI: 10.3390/ijms21041388
|View full text |Cite
|
Sign up to set email alerts
|

Role of VEGFs/VEGFR-1 Signaling and Its Inhibition in Modulating Tumor Invasion: Experimental Evidence in Different Metastatic Cancer Models

Abstract: The vascular endothelial growth factor (VEGF) family members, VEGF-A, placenta growth factor (PlGF), and to a lesser extent VEGF-B, play an essential role in tumor-associated angiogenesis, tissue infiltration, and metastasis formation. Although VEGF-A can activate both VEGFR-1 and VEGFR-2 membrane receptors, PlGF and VEGF-B exclusively interact with VEGFR-1. Differently from VEGFR-2, which is involved both in physiological and pathological angiogenesis, in the adult VEGFR-1 is required only for pathological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 295 publications
(408 reference statements)
0
99
0
1
Order By: Relevance
“…CuC dual Top inhibitors display a high antiproliferative activity. Particularly, some CuC and non-CuC are dual inhibitors of Top1 and superoxide dismutase agonist [ 88 , 207 , 208 ] or Cdk receptor, like VEGF inhibitors, involved in cancer cells proliferation [ 86 , 87 , 209 , 210 ] ( Figure 5 B). Another strategy to improve therapies is the association of a CuC with a TDP1/2 (tyrosyl-DNA-phosphodiesterase 1/2) inhibitor.…”
Section: Future Strategies For Copper Complexes As Top Inhibitorsmentioning
confidence: 99%
“…CuC dual Top inhibitors display a high antiproliferative activity. Particularly, some CuC and non-CuC are dual inhibitors of Top1 and superoxide dismutase agonist [ 88 , 207 , 208 ] or Cdk receptor, like VEGF inhibitors, involved in cancer cells proliferation [ 86 , 87 , 209 , 210 ] ( Figure 5 B). Another strategy to improve therapies is the association of a CuC with a TDP1/2 (tyrosyl-DNA-phosphodiesterase 1/2) inhibitor.…”
Section: Future Strategies For Copper Complexes As Top Inhibitorsmentioning
confidence: 99%
“…The VEGF/VEGFR-2 are important for the survival of MCF7 cells [ 56 , 57 , 58 ], but VEGFR-2 cannot be detected by Western blotting [ 59 ]. Thus, the real-time RT-PCR platform (Applied Biosystems 7500 Fast Real Time PCR System) was used to quantify the gene expression of Hsp90 and VEGFR-2 ( Table 4 ) in MCF7 cells (1 × 10 6 cells), following treatment with HAA 2020 (500, 2500, 5000 nM), dinaciclib (5, 25, 50 nM), and their combination for 24 h, as previously reported [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…These are further counted upon modifying the bioavailability of VEGF-A in the tumors by matrix metalloproteinases processing. Adding to this fact, antibody-mediated neutralization of angiopoietin 2, the ligand for the Tie2 receptor, or macrophage depletion blocks tumor angiogenesis as well as limits tumor progression in a mouse model of breast cancer [26]. Several studies conducted on the patients having cancer in liver cells showed that the marginal macrophage density is different from the macrophage density present inside the tumor of the liver although they are directly associated along with the vascular invasion, tumor multiplicity, and also fibrous capsule formation.…”
Section: Role Of Macrophage In Tumor Progressionmentioning
confidence: 99%